CONTEMPORARY LIBRARY SERVICES FOR SCIENTISTS: АССОRDING TO SOCIOLOGICAL RESEARCH - Myrgorodska, Alla I.; Petrenko, Olena A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article presents the results of a questionnaire conducted during the seminar by Scientific and Technical Library of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan. The survey was conducted in order to identify the level of implementation of the digital initiatives of scientific communication in higher educational institutions of Ukraine; improvement of library and information services for library users in contemporary conditions.